Multiple Orthokeratinized Odontogenic Cysts: A Case Report - Cheng, Yi-Shing Lisa (Head Neck Pathol, 2014)
The purpose of this report is to document the clinical, radiographic, pathological and molecular findings of the first case of multiple orthokeratinized odontogenic cysts (OOCs). Multiple odontogenic keratocysts are one of the major features of nevoid basal cell carcinoma syndrome (NBCCS), and loss of heterozygosity in the PTCH gene, the culprit gene for NBCCS, has recently been found in sporadic OOC cases. Therefore, in this presenting case, we also investigated the possibility that this patient might also have NBCCS, by comparing the available clinical information and the molecular findings of this case to the diagnostic criteria for NBCCS (as proposed by the First International Colloquium on NBCCS in 2011). However, this patient with multiple OOCs showed no evidence of having NBCCS. This conclusion supports the findings from previous case series based on sporadic cases that OOC does not appear to be associated with NBCCS.